Trusting records in the Cloud - Duranti, Luciana; Rogers, Corinne (Facet, 2019)
Trusting Records in the Cloud presents key findings of InterPARES Trust, an international research project that has investigated issues of trust in, and trustworthiness of records and data online, with respect to privacy, accessibility, portability, metadata and ownership. The project has produced theoretical and methodological frameworks for the development of local, national and international policies, procedures, regulations, standards and legislation, to ensure public trust grounded on evidence of good governance, strong digital economy and persistent digital memory. Topics include: risks and remedies to the contracts the public must enter into with service providers implementing retention and disposition schedules in the cloud understanding the role of metadata in cloud services for chain of custody rethinking issues of appraisal, arrangement and description preservation as a series of services implementable by a variety of preservation actors information governance, risk management, and authentication practices and technologies. Readership: This book is essential reading for records and archives managers, information professionals and organizations that are using or intend to use the cloud for the creation, management and preservation of their information; records and archives students and educators; individuals working in the academic, government and private sectors, and members of the public concerned about their personal information in the cloud.